2009
DOI: 10.1177/1477878509343736
|View full text |Cite
|
Sign up to set email alerts
|

Too cool for school?

Abstract: Homeschooling can be a last resort for frustrated families where gifted children are not having their complex needs met through mainstream schooling. Unlike many other groups of homeschoolers, parents of highly able children take this option for pragmatic reasons rather than as a kind of moral stance. This article explores some of the ways that standard schools fail gifted children and presents the perspectives of families who have made the choice to remove their gifted children from the mainstream education s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 8 publications
(4 reference statements)
1
4
0
Order By: Relevance
“…School quality and individualization concerns are consistent with findings from previous studies of homeschool families (Kunzman & Gaither, 2020;Murphy, 2014). In our sample, parents' desire for appropriate pacing and academic acceleration also aligns with previous findings and recommendations (Jolly et al, 2013;Winstanley, 2009).…”
Section: Theme 2: Academicssupporting
confidence: 91%
See 2 more Smart Citations
“…School quality and individualization concerns are consistent with findings from previous studies of homeschool families (Kunzman & Gaither, 2020;Murphy, 2014). In our sample, parents' desire for appropriate pacing and academic acceleration also aligns with previous findings and recommendations (Jolly et al, 2013;Winstanley, 2009).…”
Section: Theme 2: Academicssupporting
confidence: 91%
“…Research focusing on homeschooling of children identified as gifted is sparse (see Dennison et al, 2020; Jolly et al, 2013; Jolly & Matthews, 2017, 2018, 2020a, 2020b; Logan, 2018; Winstanley, 2009). Families of gifted children have indicated that their decision to homeschool came after multiple unsatisfactory experiences with traditional schools (Jolly et al, 2013).…”
Section: Homeschooling Gifted Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the dearth of empirical literature on gifted homeschoolers and their families (Winstanley, 2009), the primary purpose of the present exploratory research is to set the stage for further research. We also attempt to better understand the pragmatic reasons that underlie decisions by families of gifted homeschoolers to homeschool.…”
mentioning
confidence: 99%
“…Home-schooling is strictly regulated by the government in terms of attendance, progression and continuous assessment; however, parents are solely responsible for the decisions regarding their children's education. This firmly establishes their control and sovereignty within the home-schooling environment (Winstanley, 2009). Parents can take over the role of mentors or use the services of a certified teacher to provide instruction using an accredited curriculum (Moore et al, 2004).…”
Section: Introductionmentioning
confidence: 99%